Optimal initial antibiotic regimen for the treatment of acute appendicitis: a systematic review and network meta-analysis with surgical intervention as the common comparator. (1st April 2021) - Wang, Chih-Hung; Yang, Chi-Chun; Hsu, Wan-Ting; Qian, Frank; Ding, Julia; Wu, Han-Ping; Tsai, Jih-Jin; Yang, Chia-Jui; Su, Ming Yang; Chen, Shyr-Chyr; Lee, Chien-Chang
Abstract: Background: The optimal antibiotic regimen for the medical management of acute appendicitis remains unknown due to a lack of head-to-head comparisons between different antibiotic regimens. Methods: We systematically searched the PubMed, EMBASE, Scopus and Cochrane Central Register of Controlled Trials databases from their inception through to August 2020. We selected randomized controlled trials (RCTs) or observational studies comparing antibiotic therapy and appendectomy as the initial treatment for adult or paediatric patients with acute appendicitis. We performed a Bayesian network meta-analysis (NMA) to obtain the indirect comparison results between different antibiotic regimens by employing the group managed by surgery as a common comparator. Antibiotic regimens were classified into three categories: those including a carbapenem; those including a cephalosporin; and those including a β-lactam/β-lactamase inhibitor combination. Results: A total of 9 RCTs (adults, n  = 8; paediatrics, n  = 1) and 12 observational studies (adults, n  = 3; paediatrics, n  = 9) were included in the NMA, with a total of 4551 patients. The most commonly administered regimen was a β-lactam/β-lactamase inhibitor combination (9/21; 43%), followed by a cephalosporin (7/21; 33%) or a carbapenem (5/21; 24%). The NMA indicated that surgery significantly increased 1 year treatment success, compared with cephalosporins [OR: 16.79; 95% credible interval: 3.8–127.64] or β-lactam/β-lactamase inhibitor combinations (OR: 19.99; 95% credible interval: 4.87–187.57), but not carbapenems (OR: 3.50, 95% credible interval: 0.55–38.63). In contrast, carbapenems were associated with fewer treatment-related complications compared with surgery (OR: 0.12; 95% credible interval: 0.01–0.85). Conclusions: Carbapenems might be recommended as the initial antibiotic regimen for the non-operative management of adult patients with acute appendicitis. Nevertheless, due to the imprecise estimates in our NMA, additional RCTs are needed to corroborate these findings, especially for paediatric patients.